The triple role of potatoes as a source of cash, food, and employment: Effects on nutritional improvement in Rwanda - Blanken, Jürgen; von Braun, Joachim; de Haen, Hartwig (International Food Policy Research Institute, 1994)
Potatoes, of all food crops, had the fastest average annual growth rate of production in Rwanda between 1970 and 1985: 6.8 percent. This increase in potato production was mainly brought about by a rapid expansion of the cultivated and harvested acreage, which grew by 6.7 percent per year during the same period, whereas average yields only slightly increased by 0.1 percent per year. In 1983, potato production covered an estimated 3.3 percent of the total harvest food crop acreage, and contributed to 3.1 percent of total calorie production (Delepierre 1985).